STUDENTS’ INTERESTS IN LEARNING ENGLISH AS A FOREIGN LANGUANGE - Sari, Indah (UIN Sumatera Utara, 2023)
This study aimed to elucidate and explain about students’ interests in English learning. Then, this study applied the descriptive qualitative method which described an inquiry process of understanding a social or human problem, based on building a complex, holistic, formed with words. the subjects of this study were 42 students of second semester at Institut Teknologi Kelapa Sawit Indonesia in Medan. Moreover, the technique of data collection was administering the open questionnaire regarding students’ interests in English learning. Then, the technique of data analysis used Miles, Huberman, and Saldana steps such as 1) data condensation, data display, and 3) data verification. The findings showed that the students had great interests in English learning that indicated by enjoying and being happy during the learning process, focusing and being enthusiastic when doing the activities, taking some notes of the English lesson, being motivated and active in the classroom, reviewing the previous material and trying to improve the English skills. Furthermore, they had great interests in English learning because of the interesting, comfortable, and enjoyable teaching. Moreover, they felt English was very important and they wanted to improve their skills in English. Then, the findings have the implication and contribution to the development of learning English as a foreign language in Indonesia.